The Effect of Discovery Learning Model Integrated with Javalab Simulation On Students' Conceptual Understanding and Learning Interest in Chemical Bonding Material - Simanjuntak, Melisa Br; Rahmi, Ayu; Fakhrah, Fakhrah; Muliaman, Agus; Imanda, Riska (Electronic Journal of Education, Social Economics and Technology, 2026)
Students often experience difficulties in understanding chemical concepts, which are generally abstract, such as chemical bonding material. The primary objective of the current research is to ascertain the specific impact resulting from the adoption of the Discovery Learning framework integrated with Javalab simulation of students' conceptual understanding as well as their interest in learning chemical bonding material within SMA Negeri 2 Sawang.  The investigative approach employed was a Pre-Experimental methodology that specifically adopted an Intact Group Comparison design structure. The entire population involved in this academic study comprised every student currently enrolled in class XI SMA Negeri 2 Sawang, with the sample determined by Saturated Sampling, consisting of class XI-1 as the treatment group and class XI-2 as the comparison group. The techniques utilized for the collection of necessary data included test instruments (posttest) to measure concept understanding and questionnaires to measure student motivation toward their studies. The purpose of analyzing used the Independent Sample T-test. The findings demonstrated that there was a meaningful impact existed from the Discovery Learning approach integrated with Javalab simulation on students' concept understanding (Sig. 2-tailed 0.002 0.05) and their educational curiosity (Sig. 2-tailed 0.000 0.05). The application of this model can visualize abstract concepts while simultaneously increasing the level of student involvement throughout the entire learning process.